2022
DOI: 10.31744/einstein_journal/2022ao6704
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with multidrug-resistant bacteria in healthcare-associated infections: a pediatric intensive care unit case-control study

Abstract: Objective: To investigate the prevalence of factors related to healthcare-associated infections, caused by multidrug-resistant bacteria, in a pediatric intensive care unit. Methods: A retrospective case-control study conducted from January 1, 2007 to December 31, 2018, in São Paulo (SP), Brazil. The study was carried out at the pediatric intensive care unit of a highcomplexity, tertiary care general hospital. The study included patients aged 1 month to 19 years, admitted to the pediatric intensive care unit, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(48 reference statements)
1
2
0
1
Order By: Relevance
“…5 Children are more susceptible than adults because of their immature immune systems and impaired innate and adaptive defenses caused by acute illnesses. 6 A recent multicenter pediatric study in Europe showed that HAIs are the highest in children in the first year of life, underscoring the importance of bloodstream infections as the most common type of HAI in children, similar to previous pediatric studies. 2,3 The identification of pediatric-specific risk factors for infections and solutions needed to prevent pediatric HAIs have not been thoroughly studied.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…5 Children are more susceptible than adults because of their immature immune systems and impaired innate and adaptive defenses caused by acute illnesses. 6 A recent multicenter pediatric study in Europe showed that HAIs are the highest in children in the first year of life, underscoring the importance of bloodstream infections as the most common type of HAI in children, similar to previous pediatric studies. 2,3 The identification of pediatric-specific risk factors for infections and solutions needed to prevent pediatric HAIs have not been thoroughly studied.…”
supporting
confidence: 78%
“…Numerous risk variables, such as underlying diseases, serious illnesses, increased duration of hospital stay, gastrointestinal surgeries, and invasive devices, have been linked to nosocomial bloodstream infections (nBSIs) due to drug-resistant bacteria in adult studies 5 . Children are more susceptible than adults because of their immature immune systems and impaired innate and adaptive defenses caused by acute illnesses 6 . A recent multicenter pediatric study in Europe showed that HAIs are the highest in children in the first year of life, underscoring the importance of bloodstream infections as the most common type of HAI in children, similar to previous pediatric studies 2,3 .…”
mentioning
confidence: 99%
“…This is undesirable: an increased frequency of infection is associated with reduced health-related quality of life in patients with immunodeficiency 9 and incurs additional healthcare costs. Furthermore, the prevalence of antibiotic resistance organisms is increased in individuals with immunodeficiency 10,11 ; antibiotic stewardship should also be considered in IgRT dose decision-making.…”
Section: Dose Reductions In Immunoglobulin Replacement Are Associated...mentioning
confidence: 99%
“…O aumento na detecção de bactérias MDR em pacientes de UTI pediátrica, reportado por diversos autores (Le Doare et al, 2015;Oliveira, P. et al, 2019;Silva et al, 2022), é um fator extremamente limitante na sobrevida de RN (Zhang et al, 2022). Nesse cenário, o monitoramento contínuo do perfil de resistência das cepas isoladas no ambiente hospitalar torna-se fundamental.…”
Section: Introductionunclassified